Regio- and Stereoselective Synthesis of Spirooxindoles via Mizoroki–Heck Coupling of Aryl Iodides - Adeyemi, Ahmed; Wetzel, Alexander; Bergman, Joakim; Brånalt, Jonas; Larhed, Mats (Synlett, 2019)
A method for highly regio- and stereoselective intramolecular Mizoroki–Heck 5-exo cyclization of aryl iodides to the corresponding spirooxindoles has been developed. Electron-rich and electron-deficient aryl iodide precursors were selectively ring-closed with high stereoselectivity and good yields. The double-bond position in the cyclopentene ring was controlled by careful choice of reaction conditions. These rare spiro compounds were further functionalized to rigidified unnatural amino acid derivatives by a subsequent gas-free Pd(0)-catalyzed alkoxycarbonylation, followed by selective O- and N-deprotections.
Keywords: spirooxindoles; Mizoroki–Heck; cyclization; carbonylation